The anabolic effect of inorganic polyphosphate on chondrocytes is mediated by calcium signalling. Issue 2 (29th March 2021) - Gawri, Rahul; Bielecki, Ryszard; Salter, Eric W.; Zelinka, Alena; Shiba, Toshikazu; Collingridge, Graham; Nagy, Andras; Kandel, Rita A.
Abstract: Inorganic polyphosphates (polyP) are polymers composed of phosphate residues linked by energy‐rich phosphoanhydride bonds. As polyP can bind calcium, the hypothesis of this study is that polyP enters chondrocytes and exerts its anabolic effect by calcium influx through calcium channels. PolyP treatment of cartilage tissue formed in 3D culture by bovine chondrocytes showed an increase in proteoglycan accumulation but only when calcium was also present at a concentration of 1.5 mM. This anabolic effect could be prevented by treatment with either ethylene glycol‐bis(β‐aminoethyl ether)‐N, N, N', N'‐tetraacetic acid or the calcium channel inhibitors gadolinium and nifedipine. Calcium and polyP cotreatment of chondrocytes in monolayer culture resulted in calcium oscillations that were polyP chain length specific and were inhibited by gadolinium and nifedipine. The calcium influx resulted in increased gene expression of sox9, collagen type II, and aggrecan which was prevented by treatment with either calphostin, an inhibitor of protein kinase C, and W7, an inhibitor of calmodulin; suggesting activation of the protein kinase C‐calmodulin pathway. Tracing studies using  4′, 6‐diamidino‐2‐phenylindole, Mitotracker Red, and/or Fura‐AM staining showed that polyP was detected in the nucleus, mitochondria, and intracellular vacuoles suggesting that polyP may also enter the cell. PolyP colocalizes with calcium in mitochondria. This study demonstrates that polyP requires the influx of calcium to regulate chondrocyte matrix production, likely via activating calcium signaling. These findings identify the mechanism regulating the anabolic effect of polyP in chondrocytes which will help in its clinical translation into a therapeutic agent for cartilage repair. Abstract : Schematic showing that calcium and polyP causes calcium fluxes which correlates with involvement of protein kinase C (PKC) and calmodulin which was associated with increased production of proteoglycan (GAG). polyP can be detected in nucleus, mitochondria and vacuoles.